Access Control Points: Reducing a Possible Blast Impact by Meandering - Martin Larcher; Georgios Valsamos; Vasilis Karlos (Advances in Civil Engineering)
In response to the heightened terror threat in recent years, there is an increasing interest in the introduction of access control zones at sites that are characterized by an increased likelihood of being the target of a terrorist attack, as latest data reveal that unprotected areas of mass congregation of people have become attractive to terrorist groups. Such control zones could be located within the building that has to be protected or attached to it. The elevated security needs for these areas call for a design that will consider the risk of internal explosive events. The purpose of this article is to outline a strategy for limiting the consequences of an internal blast, while guaranteeing that the produced blast wave does not propagate into vulnerable areas. In particular, the focus is on the introduction of a protective wall system in the form of a meander that allows unobstructed access of the public and at the same time reduces the possible blast inflow to the building's interior. The performed numerical simulations show that the proposed strategy yields much smaller injury risk areas compared to a design without the addition of protective walls and is recommended for upgrading the security of buildings.